Plan and Market in China's Agricultural Commerce - Sicular, Terry (Journal of Political Economy, 1988)
This article examines interactions between markets and state commercial planning in the context of China's agricultural sector. It begins with a discussion of recent trends in agricultural planning and commerce in China and then presents a theoretical model that analyzes the way that a mixed commercial system of the sort observed in China functions. The theoretical analysis suggests that a mixed system is sustainable and can have desirable efficiency and distributional effects. Markets, however, limit the range of sustainable plans, and in the presence of markets, state planning may no longer directly influence production and consumption behavior.